Evaluating the benefits of national adaptation to reduce climate risks and contribute to the Sustainable Development Goals. (September 2022) - Fuldauer, Lena I.; Adshead, Daniel; Thacker, Scott; Gall, Sarah; Hall, Jim W.
Abstract: Scaling up national climate adaptation under the Paris Agreement is critical not only to reduce risk, but also to contribute to a nation's development. Traditional adaptation assessments are aimed at evaluating adaptation to cost-effectively reduce risk and do not capture the far-reaching benefits of adaptation in the context of development and the global Sustainable Development Goals (SDGs). By grounding adaptation planning in an SDG vision, we propose and demonstrate a methodological process that for the first time allows national decision-makers to: i) quantify the adaptation that is needed to safeguard SDG target progress, and ii) evaluate strategies of stakeholder-driven adaptation options to meet those needs whilst delivering additional SDG target co-benefits. This methodological process is spatially applied to a national adaptation assessment in Ghana. In the face of the country's risk from floods and landslides, this analysis identifies which energy and transport assets to prioritise in order to make the greatest contribution to safeguarding development progress. Three strategies ('built', 'nature-based', 'combined SDG strategy') were formulated through a multi-stakeholder partnership involving government, the private sector, and academia as a means to protect Ghana's prioritised assets against climate risk. Evaluating these adaptation strategies in terms of their ability to deliver on SDG targets, we find that the combined SDG strategy maximises SDG co-benefits across 116 targets. The proposed methodological process for integrating SDG targets in adaptation assessments is transferable to other climate-vulnerable nations, and can provide decision-makers with spatially-explicit evidence for implementing sustainable adaptation in alignment with the global agendas.